Abnormal brain functional connectivity coupled with hypoperfusion measured by Resting-State fMRI: An additional contributing factor for cognitive impairment in patients with Alzheimer's disease. (30th July 2019) - Zhang, Bing; Hua, Rui; Qing, Zhao; Ni, Ling; Zhang, Xin; Zhao, Hui; Liu, Renyuan; Lu, Jiaming; Wu, Sichu; Xu, Yun; Zhu, Bin; Wan, Suiren; et al.
Highlights : TSA methodology is a promising technique for detecting hypoperfusion. Abnormal FC might be associated with hypoperfusion in dementia patients. Abnormal FC show significant negative correlation with MMSE in MCI patients. Hypoperfusion may affect cognitive state via abnormal FC. Abstract: The contribution of hypoperfusion to abnormal functional connectivity in Alzheimer's disease (AD) and mild cognitive impairment (MCI) remains unclear. In this study, we investigated the potential association between brain perfusion and functional connectivity (FC), and its effects on the cognitive impairment among AD, MCI, and normal controls (NC). One-time acquisition of resting-state functional magnetic resonance imaging (rs-fMRI) was used to study brain perfusion and FC. Compared to the NC, the perfusion in the left temporal lobe showed significantly lower in AD, and bilateral hypoperfusion in the frontal lobe showed in MCI. Using these hypoperfusion areas as seed regions, we found that FC between the left inferior temporal gyrus and medial frontal-cingulate regions in AD patients was significantly lower than that in NCs. The FC between the right medial superior frontal gyrus and left parietal lobe in MCI patients was significantly higher than that in NCs. Additionally, the FC between the right medial superior frontal gyrus and the left superior parietal gyrus were found to be correlated significantly and negatively with mini-mental state examination (MMSE) scores in MCI patients. In conclusion, hypoperfusion may affect cognitive states via abnormal FC as an additional factor contributing to cognitive impairment.